"As soon as people hear that word…": associative stigma among clinicians working with people with serious mental illness. Issue 1 (19th March 2018) - Vayshenker, Beth A.; DeLuca, Joseph; Bustle, Timothy; Yanos, Philip
Abstract : Purpose: Stigma by association occurs when members affiliated with a marginalized group become discredited themselves. The purpose of this paper is to explore associative stigma among mental health (MH) clinicians working with individuals diagnosed with serious mental illness (SMI). Design/methodology/approach: In total, 47 eligible service providers completed an online qualitative study, with open-ended questions about areas touching on associative stigma such as assumptions about the MH profession, personal experiences of work-related stigma, and ways of coping. Findings: The data revealed that MH clinicians commonly endorse experiences of associative stigma. The following themes were derived: experiences of stigma in describing the profession to others, media portrayal of MH professionals, assumptions about the field, ascriptions of personal characteristics, job devaluation, means of coping with associative stigma, and impact of associative stigma on work on clients. Originality/value: This is the first qualitative study to examine the phenomenon of associative stigma with MH clinicians. This study suggests that MH providers working with people with SMI do encounter associative stigma when discussing their profession with community members. Professionals discussed encountering the stereotype that the work that they do is dangerous, that it is something "unwanted" and that it does not require much skill but could be done by anyone. Associative stigma could be an important component in the understanding of factors related to professional burnout.